Identification and Characterization of Four Azole-Resistant erg3 Mutants of Candida albicans - Martel, Claire M. (American Society for Microbiology (ASM), 2010)
Sterol analysis identified four Candida albicans erg3 mutants in which ergosta 7,22-dienol, indicative of perturbations in sterol Δ(5,6)-desaturase (Erg3p) activity, comprised >5% of the total sterol fraction. The erg3 mutants (CA12, CA488, CA490, and CA1008) were all resistant to fluconazole, voriconazole, itraconazole, ketoconazole, and clotrimazole under standard CLSI assay conditions (MIC values, ≥256, 16, 16, 8, and 1 μg ml(−1), respectively). Importantly, CA12 and CA1008 retained an azole-resistant phenotype even when assayed in the presence of FK506, a multidrug efflux inhibitor. Conversely, CA488, CA490, and three comparator isolates (CA6, CA14, and CA177, in which ergosterol comprised >80% of the total sterol fraction and ergosta 7,22-dienol was undetectable) all displayed azole-sensitive phenotypes under efflux-inhibited assay conditions. Owing to their ergosterol content, CA6, CA14, and CA177 were highly sensitive to amphotericin B (MIC values, <0.25 μg ml(−1)); CA1008, in which ergosterol comprised <2% of the total sterol fraction, was less sensitive (MIC, 1 μg ml(−1)). CA1008 harbored multiple amino acid substitutions in Erg3p but only a single conserved polymorphism (E266D) in sterol 14α-demethylase (Erg11p). CA12 harbored one substitution (W332R) in Erg3p and no residue changes in Erg11p. CA488 and CA490 were found to harbor multiple residue changes in both Erg3p and Erg11p. The results suggest that missense mutations in ERG3 might arise in C. albicans more frequently than currently supposed and that the clinical significance of erg3 mutants, including those in which additional mechanisms also contribute to resistance, should not be discounted.